The Impact of Matching to Psychotherapy Preference on Engagement in a Randomized Controlled Trial for Patients With Advanced Cancer - Marziliano, Allison; Applebaum, Allison; Moyer, Anne; Pessin, Hayley; Rosenfeld, Barry; Breitbart, William (Frontiers in Psychology, 2021)
Objective: This study examined whether patients who were randomly assigned to their preferred therapy arm had stronger engagement with their treatment than those who were randomly assigned to a non-preferred therapy arm. Method: Data were drawn from a RCT comparing Individual Meaning-Centered Psychotherapy (IMCP), with Individual Supportive Psychotherapy (ISP), in patients with advanced cancer. Treatment engagement was operationalized as patients' perceptions of the therapeutic alliance with their therapist and therapy sessions attended. Two 2 by 2 Analysis of Variance (ANOVA) models were used, with treatment preference (IMCP vs. ISP) and treatment assignment (IMCP vs. ISP) as the independent variables and working alliance and number of sessions attended as outcome variables. Results: Patients who preferred and were assigned to IMCP reported a significantly stronger alliance than those who preferred IMCP but were assigned to ISP. Conclusions: The findings from this study have broader implications for research on psychotherapy beyond the appeal of IMCP in advanced cancer patients. Patients who prefer a novel psychotherapy that they cannot engage in elsewhere, but receive the standard treatment may experience weaker alliance than patients who prefer the standard but receive the novel therapy. Trial registration:Clinicaltrial.gov ID: NCT01323309